STRATEGI PEMRINTAH DAERAH DALAM PENANGANAN ANAK PUTUS SEKOLAH DI DESA LATIMOJONG KECAMATAN BUNTU BATU KABUPATEN ENREKANG - Lorensa, Dina; Ramadhan , Muh.Rohady; Jabbar, Abdul (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to explore the strategies implemented by the local government in addressing the issue of school dropouts. Using a qualitative approach, this research seeks to deeply understand the factors contributing to school dropouts and the steps taken by the local government to tackle this problem. Data collection was carried out through observations, in-depth interviews, and document analysis. The findings show that the local government's strategies include a multi-sectoral approach, such as lobbying relevant agencies to provide educational and sports facilities, offering educational assistance, and improving the accessibility of educational infrastructure. Additionally, the local government collaborates with the local community to create an environment that supports the sustainability of children's education. Challenges faced include budget limitations, insufficient land for building educational facilities, and inadequate road access. Despite these challenges, the collaboration between the local government and the community has shown positive results in reducing the number of school dropouts and enhancing the quality of education in the area.